Re-estimating the interconnectedness between the demand of energy consumption, income, and sustainability indices - Ozcan, Burcu; Tzeremes, Panayiotis; Dogan, Eyup (Springer Heidelberg, 2019)
In this study, we analyze the time-varying causality linkages between energy consumption, economic growth, and environmental degradation in 33 Organization for Economic Co-operation and Development countries, spanning the period 2000 to 2013. The curve causality approach provides evidence of a significant environmental Kuznets curve in 25 countries in the case of the ecological footprint and in 23 countries in the case of the Environmental Performance Index. However, out of them, only Italy, Slovakia, and South Korea have traditional environmental Kuznets curve, in the form of an inverted U-shaped curve. For the remaining countries, different forms of curves are valid. In particular, an N-shaped curve appears to be valid between income and environmental degradation for nearly half of the sample, i.e., for Austria, Belgium, Chile, Estonia, Finland, France, Germany, Hungary, Luxembourg, Netherlands, Sweden, Switzerland, New Zealand, Turkey, and the USA. Additionally, bidirectional causality relationships are confirmed among all covariates in most countries. In view of the results, some crucial policy implications would be suggested, such as sustainable development that aims to make a balance between economic growth and environmental protection.
Keywords: Environmental Kuznets curve; Energy consumption; Sustainability indices; Economic growth; Time-varying causality